Diagnostic accuracy of D-dimer in patients at high-risk for splanchnic vein thrombosis: A systematic review and meta-analysis. Issue 207 (November 2021) - Riva, Nicoletta; Attard, Laura Maria; Vella, Kevin; Squizzato, Alessandro; Gatt, Alex; Calleja-Agius, Jean
Abstract: Background: D-dimer is included in the diagnostic algorithm for deep vein thrombosis and pulmonary embolism. However, its role in the diagnosis of splanchnic vein thrombosis (SVT) is still controversial. The aim of this study was to evaluate the diagnostic accuracy of D-dimer for SVT. Methods: We performed a systematic review of the literature with meta-analysis (PROSPERO protocol registration number: CRD42020184300). The electronic databases MEDLINE, EMBASE, and CENTRAL were searched from inception to March 2021 week 4. Studies which evaluated D-dimer accuracy for SVT in any category of patients were selected. The index test was any D-dimer assay; the reference standard was any radiological imaging. The QUADAS-2 checklist was used for the risk of bias assessment. A bivariate random-effects regression model was used to calculate summary estimates of sensitivity and specificity. Results: 12 studies (with a total of 1298 patients) evaluating the accuracy of D-dimer in patients at high risk of SVT (surgical patients, patients with liver cirrhosis or hepatocellular carcinoma) were included. None of the included studies was at low risk of bias. The weighted mean prevalence of SVT was 33.4% (95% CI, 22.5–45.2%, I 2 = 94.8%). D-dimer accuracy was expressed by sensitivity 96% (95% CI, 72–100%); specificity 25% (95% CI, 5–67%); positive likelihood ratio 1.3 (95% CI, 0.9–1.9); negative likelihood ratio 0.16 (95% CI, 0.03–0.84); area under the ROC curve 0.80 (95% CI, 0.76–0.83). Conclusions: D-dimer seems to have high sensitivity in the diagnosis of patients at high-risk for SVT. However, there is a strong need for more robust evidence on this topic. Graphical abstract: Unlabelled Image Highlights: D-dimer role in the diagnosis of splanchnic vein thrombosis (SVT) is controversial. The diagnostic accuracy of D-dimer for SVT was evaluated in a systematic review. D-dimer showed high sensitivity in patients at high-risk for SVT. There was high risk of bias and high heterogeneity in the published literature.